Pemodelan Sistem Pakar Deteksi Dini Resiko Penularan HIV/AIDS Menggunakan Metode Dempster-Shafer - Marine Putri Dewi Yuliana; Lailil Muflikhah; Rizal Setya Perdana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Human Immunodeficiency Virus (HIV) is a disease that attacks the body immune and until now still not found a drug that can cure it. People with HIV are often regarded as a disgrace that can cause psychological pressure on patients and families around him. It is this kind of thing which can then lead to the process of AIDS happening faster. Lack of information and ignorance of the spread of this virus resulted in increasing HIV patients. Fear will be regarded as a sufferer and do not want his privacy disturbed, most people are reluctant to ask this specialist about HIV. Therefore the need for a system that can be used as a support activity solving a problem. The knowledge to be represented in the expert system is full of uncertainty and disguise. One way to overcome the problem of uncertainty can be done by using Dempster Shafer method. The result obtained from 28 existing data has an accuracy of 78%. This indicate the system can be used in the expert system for early detection of HIV/AIDS.